A Universal Model of Giftedness – an adaptation of the Munich Model. (2nd July 2016) - Jessurun, J.H.; Shearer, C.B.; Weggeman, M.C.D.P.
Abstract : The Munich Model of Giftedness (MMG) by Heller and his colleagues, developed for the identification of gifted children, is adapted and expanded, with the aim of making it more universally usable as a model for the pathway from talents to performance. On the side of the talent-factors, the concept of multiple intelligences is introduced, and the moderating factors proposed in the MMG are discussed and categorized. The environmental moderators are interpolated as to incorporate not only "school-settings" but also "work-settings".